2014
DOI: 10.1097/mpg.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

US‐Guided Percutaneous Liver Biopsy in Pediatric Liver Transplant Recipients

Abstract: The rate of complications in pediatric patients after US-guided liver biopsy is low. A range of pathological results exists between early and late posttransplantation liver biopsies. LFT and Doppler US findings are not predictors of pathological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Antagonism of FXR may promote cholestasis through all these mechanisms 4 , 10 . In line with earlier studies, 6 9 , 12 15 we found serum and liver PSs to correlate with GT, a sensitive marker of cholestasis and biliary injury 32 . In PN‐dependent patients, liver campesterol and stigmasterol also correlated with liver fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Antagonism of FXR may promote cholestasis through all these mechanisms 4 , 10 . In line with earlier studies, 6 9 , 12 15 we found serum and liver PSs to correlate with GT, a sensitive marker of cholestasis and biliary injury 32 . In PN‐dependent patients, liver campesterol and stigmasterol also correlated with liver fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…International Normalized Ratio is a valuable biomarker for prognostication and determination of organ allocation; however it is inadequate for the measurement of bleeding risk. In children undergoing liver biopsy, hemorrhagic complications can occur in 0.91-4.2% of cases and coagulopathy markers do not predict bleeding complications (36,37).…”
Section: Limitation Of Standard Hemostatic Testsmentioning
confidence: 99%
“…Previous reports of liver biopsy risk in children are predominantly retrospective, small or single center, and not transplant specific . In contrast, this report is based on prospectively collected data from two multicenter, immunosuppression withdrawal trials (WISPR [NCT00320606] and iWITH [NCT01638559]).…”
Section: Introductionmentioning
confidence: 99%